ANALYSIS OF THE EFFECT OF DIGITAL PRODUCT TYPES AND TRANSACTION FREQUENCY ON DIGITAL PRODUCT SALES IN TANGERANG THROUGH A DATA WAREHOUSE APPROACH - Wilmaya Firmandatiyas; Febrina Lusianna Manik; Sharon Sheilla Shane; Gabriella Paulita Morong; Muh. Masri Sari; Rido Dwi Kurniawan (Algebra : Jurnal Pendidikan, Sosial dan Sains, 2026)
The growth of the digital economy has made digital products such as prepaid credit, internet data, and game vouchers essential for urban communities, including in Tangerang City. This study aims to analyze the effect of digital product type and transaction frequency on digital product sales in Tangerang. A quantitative explanatory approach is applied using secondary data extracted from a retail partner’s data warehouse and processed with Python in Google Colab. The sample consists of 200 digital product transactions in October 2025, selected using total sampling. Data are analyzed using multiple linear regression and classical assumption tests. The results show that transaction frequency has a positive and significant effect on sales; prepaid credit has a negative and significant effect compared to internet data, while game vouchers have a positive and significant effect on sales. An R-squared value of 9.04% indicates that other factors also influence sales. These findings highlight the importance of leveraging data warehouses to design data-driven strategies for improving digital product sales.